Representasi Konflik Psikososial Adanya Cyberbullying pada Film Budi Pekerti: Analisis Wacana Kritis Norman Fairclough - Desas Noel Pitaloka; Chatarina Heny Dwi Surwati (Universitas Sebelas Maret (UNS), 2025)
In addition to serving as entertaining media, films are a platform to convey messages about important issues, encouraging audiences to think more critically. One such film that delivers a meaningful message on social issues is Budi Pekerti, directed by Wregas Banutheja. This film received 17 nominations at the 2023 Indonesian Film Festival (FFI), making it the most nominated film of the year. Budi Pekerti is a drama that highlights the prevalent issue of cyberbullying in today’s society. This study aims to analyze the representation of cyberbullying and understand the conflicts arising from it through the narrative and cinematic elements of the film, using Norman Fairclough's critical discourse analysis. The research employs a qualitative method, with the object of study being the film Budi Pekerti. The approach is based on Norman Fairclough's critical discourse analysis model, which consists of three dimensions: text, discourse practice, and social practice. To deepen the analysis, the study incorporates Erik Erikson's psychosocial conflict theory. The researcher collected corpus focusing on cyberbullying and the conflicts resulting from it for analysis. The findings reveal that Budi Pekerti conveys strong messages through both verbal and visual representations. Beyond these messages, the study also explores the ideology and power dynamics present within the discourse of the film Budi Pekerti.